El concepto de narración en Walter Benjamin. Consideraciones sobre las novelas del escritor zapoteco Javier Castellanos Martínez - García Hernández, Moisés (Universidad Michoacana de San Nicolás de Hidalgo, 2021)
This thesis offers a reading of the text “El narrador. Considerations on the work of Nikolai Leskov ” by the German philosopher Walter Benjamin in the light of the most important influences of all his work: the materialism of Karl Marx, certain postulates of Sigmund Freud and even a very unique conception of Jewish messianism. The narration is presented in the first instance as a craftsmanship in ruins, whose oral character is already almost extinct in Modernity and whose peak is located in the Middle Ages, and in the second instance, the narration is presented as an oral activity that draws from the involuntary memory that is caused by boredom, and therefore flourishes with better fortune in the field and in the artisanal fields, where distractions are few and boredom is constantly present. Likewise, the narrative is characterized as a chronicle of natural history, that is, of the new historical always the same: death, passion, suffering and destiny, and finally, as a discursive activity with a vocation for justice towards the suffering destiny of all that exists that leads to death, a vocation that is also manifested in its edifying spirit. In turn, the thesis proposes a reading, through this concept of narration, of the novelistic work of the zapotec writer Javier Castellanos Martínez, which comprises, in chronological order, the following novels: Wila che be ze lhao (Songs of the first-time winds) (2007b / 1994), Gaa ka chhaka ki (Relationship of exploits of the son of Lightning) (2003), Laxdao yelazeralle (The heart of desires) (2007a) and Dxiokze xha ... bene walhall (People of the same heart) (2014), read in its translation into Spanish by Javier Castellanos Martínez himself, justified by the rural environment where such novels are developed.

La presente tesis ofrece una lectura del texto “El narrador. Consideraciones sobre la obra de Nikolai Leskov” del filósofo alemán Walter Benjamin a la luz de las influencias más importantes de toda su obra: el materialismo de Karl Marx, ciertos postulados de Sigmund Freud e incluso una concepción muy singular sobre el mesianismo judío. La narración se presenta en primera instancia como una artesanía en ruinas, cuyo carácter oral se encuentra ya casi extinto en la Modernidad y cuyo auge se ubica en la Edad Media, y en segunda instancia, la narración se presenta como una actividad oral que abreva del recuerdo involuntario que es propiciado por el aburrimiento, y por ello florece con mejor fortuna en el campo y en los ámbitos artesanales, donde las distracciones son escasas y está presente constantemente el aburrimiento. Así también, la narración es caracterizada como una crónica de la historia natural, es decir, de lo nuevo histórico siempre lo mismo: la muerte, la pasión, el sufrimiento y el destino, y por último, como una actividad discursiva con una vocación por la justicia hacia el destino sufriente de todo lo existente que desemboca en la muerte, vocación que se manifiesta también en su talante edificante. A su vez, la tesis propone una lectura, por medio de ese concepto de narración, de la obra novelística del escritor zapoteco Javier Castellanos Martínez, la cual comprende, en orden cronológico, las siguientes novelas: Wila che be ze lhao (Cantares de los vientos primerizos) (2007b/1994), Gaa ka chhaka ki (Relación de hazañas del hijo del Relámpago) (2003), Laxdao yelazeralle (El corazón de los deseos) (2007a) y Dxiokze xha... bene walhall (Gente del mismo corazón) (2014), leídas en su traducción al español hecha por el mismo Javier Castellanos Martínez, lectura justificada por el ámbito rural donde se desarrollan tales novelas.
Facultad de Letras. Maestría en Estudios del Discurso
Keywords: info:eu-repo/classification/cti/4; FL-M-2021-0538; Narrativa; Teoría de la justicia; Novela indígena; Oralidad; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6313